THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING MODELS AND SOCIAL SKILLS ON STUDENT LEARNING OUTCOMES AT SD NEGERI 101788 MARINDAL I - Nizmi Putri; Reh Bungana Br. Perangin-angin; Daulat Saragi (Jurnal Ilmiah Teunuleh, 2021)
This study aims to analyze: (1) the influence of the Contextual Teaching and Learning Model is higher compared to the Direct learning model; (2) PPKn learning outcomes of students who have high social skills are higher than students who have low social skills (3) interactions between contextual teaching and learning models and social skills in influencing PPKn learning outcomes of grade 4 students. Research in the form of Quasi-Experimental Design with factorial 2x2. The instruments used are PPKn learning results test and Social Skills instrument. Data analysis using two-lane anava. The results showed: (1) There is an influence of Contextual Teaching and Learning Model on the learning outcomes of PPKn students in grade IV SD Negeri 101788 Marindal I; (2) PPKn learning outcomes of students who have high social skills are higher than students who have low social skills; (3) There is an interaction between contextual teaching and learning models and social skills towards the learning outcomes of PPKn Siswa at SD Negeri 101788 Marindal I.